Robotic variable fabric formwork. Issue 3 (12th October 2018) - Yang, Xuyou; Loh, Paul; Leggett, David
Graphical abstract: Abstract: Casting is one of the most widely used construction techniques. Complex geometries produced via computational design processes are not readily achievable through traditional rigid formwork and are subject to increased material waste. More suitable casting techniques are required to represent digital design output efficiently. This article presents a variable fabric formwork developed to work in conjunction with a 6-axis robotic arm for casting doubly curved panels based on hyperbolic paraboloid geometry. The variable formwork is designed to be extendable in length and width so that it can produce a wide range of outcomes within a single formwork. The interface established in the workflow allows the physical formwork and digital design to influence each other. The article concludes by discussing a verification method used to confirm the accuracy of the outcome. This variable fabric form-work reduces construction waste and is a more sustainable method for casting complex geometries.